Romantic loneliness as creative fuel: Romantic loneliness and personal branding mediated by reframing mechanism among Generation Z in West Java - Laurentina, Natasya Olga; Septiana, Visya (Jurnal Psikologi, 2026)
Background: Generation Z in Indonesia (27.94% of the population) faces paradoxical digital hyperconnectivity alongside escalating romantic loneliness discrepancies between desired and achieved intimacy. Personal branding has become essential in post-pandemic digital economies.Purpose: This study examined whether romantic loneliness catalyzes personal branding development through cognitive reframing mechanisms among Indonesian Generation Z.Method: This sequential explanatory mixed-methods study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) with 151 Generation Z participants aged 20-29 years in West Java. The sample size satisfied the ten-times rule for PLS-SEM with post-hoc power analysis (>.80 for medium effect sizes). Instruments demonstrated adequate reliability (Cronbach's α = .696-.863; AVE>.59). Five participants underwent semi-structured interviews using thematic analysis.Findings: Romantic loneliness significantly predicted reframing mechanisms (β = .777, p < .001), which subsequently influenced personal branding (β = .461, p = .002), with reframing as a significant partial mediator. Qualitative analysis revealed three adaptive pathways: productivity redirection, supportive network cultivation, and existential self-prioritization.Implication: These findings demonstrate that romantic loneliness, when cognitively reframed, functions as a transformative resource for authentic personal branding. Results inform psychosocial interventions emphasizing reframing competency in educational curricula and youth programs.